ANALYSIS OF THE ACCOUNTABILITY OF CRIMINAL ACTIVITIES IN THE EIGHT OF THE LUWAK POWDER COFFEE IN PD. SUMBER BUANA ABADI (Study of Decision Number 307 / Pid.B / 2018 / PN.Kla) - Pratama, Ari (Progressive Law Review, 2019)
One form of embezzlement is in the Decision of the Kalianda District Court of South Lampung Number 307 / Pid.B / 2018 / PN.Kla which states that Defendant Selamet Riyadi Bin Tugino has been proven legally and convincingly guilty of committing a criminal offense " The problem in the research is why the perpetrators committed the crime of embezzling civet coffee in PD. Sumber Buana Abadi based on Decision Number 307 / Pid.B / 2018 / PN.Kla and how the responsibility of perpetrators of criminal acts of embezzlement of civet coffee in PD. Sumber Buana Abadi based on Decision Number 307 / Pid.B / 2018 / PN.Kla. The research method uses a normative and empirical juridical approach, where the normative juridical approach is carried out by studying legal norms or rules, legal principles, while the empirical approach is conducted by direct interviews with informants who will relate to research problems, data analysis used is qualitative juridical. The results of the study showed that the causes of the perpetrators committed the crime of embezzling civet coffee in PD. Sumber Buana Abadi, based on Decision Number 307 / Pid.B / 2018 / PN.Kla, is a mentality of workers, a fulfillment of life necessities, an intention and opportunity and a greedy attitude from humans. The most dominant factor is the urgent need for money from the perpetrators. Criminal liability perpetrators of criminal acts of embezzlement of civet coffee in PD. Sumber Buana Abadi based on Decision Number 307 / Pid.B / 2018 / PN.Kla is where the defendant Selamet Riyadi Bin Tugino has been proven legally and convincingly guilty of committing a criminal offense "Also Participating in Crime of Emblem". Sentenced to Defendant because of that with imprisonment for 10 (ten) months. Determine the period of arrest and detention that has been carried out by the Defendant to be deducted entirely from the sentence handed down. Determine the Defendant to remain detained. As well as imposing on the Defendant to pay court fees in the amount of Rp. 2,000 (two thousand rupiah). Saran, it is expected that the Judge in carrying out consideration prioritizes a sense of justice for victims, defendants and the public. It is expected that the Public Prosecutor in applying the criminal or in giving a claim to the defendant must be in accordance with the actions of the defendant because this is the judge's reference in making his decision.